Usefulness of the delta neutrophil index to predict 30-day mortality in patients with ST segment elevation myocardial infarction. Issue 1 (December 2017) - Kong, Taeyoung; Kim, Tae; Park, Yoo; Chung, Sung; Lee, Hye; Hong, Jung; Lee, Jong; You, Je; Park, Incheol
Abstract This study aimed to evaluate the association between the delta neutrophil index (DNI), which reflects immature granulocytes, and the severity of ST-elevation myocardial infarction (STEMI), as well as to determine the significance of the DNI as a prognostic marker for early mortality and other clinical outcomes in patients with STEMI who underwent reperfusion. This retrospective, observational cohort study was conducted using patients prospectively integrated in a critical pathway program for STEMI. We included 842 patients diagnosed with STEMI who underwent primary percutaneous coronary intervention (pPCI). Higher DNI values at time-I (within 2 h of pPCI; hazard ratio [HR], 1.075; 95% confidence interval [CI]: 1.046–1.108; p < 0.001) and time-24 (24 h after admission; HR, 1.066; 95% CI: 1.045–1.086; p < 0.001) were significant independent risk factors for 30-day mortality. Specifically, DNI values >2.5% at time-I (HR, 13.643; 95% CI: 8.13–22.897; p < 0.001) and > 2.9% at time-24 (HR, 12.752; 95% CI: 7.308–22.252; p < 0.001) associated with increased risks of 30-day mortality. In conclusion, an increased DNI value, which reflects the proportion of circulating immature granulocytes in the blood, was found to be an independent predictor of 30-day mortality and poor clinical outcomes in patients with acute STEMI post-pPCI.